Human sperm mitochondrial DNA copy numbers and deletion rates: Comparing persons living in two urban industrial agglomerations differing in sources of air pollution - Vozdova, Miluse; Kubickova, Svatava; Kopecka, Vera; Sipek, Jaroslav; Rubes, Jiri (Mutation research. Genetic toxicology and environmental mutagenesis, 2024)
Persons living in industrial environments are exposed to levels of air pollution that can affect their health and fertility. The Czech capital city, Prague, and the Ostrava industrial agglomeration differ in their major sources of air pollution. In Prague, heavy traffic produces high levels of nitrogen oxides throughout the year. In the Ostrava region, an iron industry and local heating are sources of particulate matter (PM) and benzo[a]pyrene (B[a]P), especially in the winter. We evaluated the effects of air pollution on human sperm mitochondrial DNA (mtDNA). Using real-time PCR, we analysed sperm mtDNA copy number and deletion rate in Prague city policemen in two seasons (spring and autumn) and compared the results with those from Ostrava. In Prague, the sperm mtDNA deletion rate was significantly higher in autumn than in spring, which is the opposite of the results from Ostrava. The sperm mtDNA copy number did not show any seasonal differences in either of the cities; it was correlated negatively with sperm concentration, motility, and viability, and with sperm chromatin integrity (assessed with the Sperm Chromatin Structure Assay). The comparison between the two cities showed that the sperm mtDNA deletion rate in spring and the sperm mtDNA copy number in autumn were significantly lower in Prague vs. Ostrava. Our study supports the hypothesis that sperm mtDNA deletion rate is affected by the composition of air pollution. Sperm mtDNA abundance is closely associated with chromatin damage and standard semen characteristics.
Keywords: Police; mitochondriální DNA; DNA, Mitochondrial; Male; DNA Copy Number Variations; Particulate Matter; pevné částice; Sperm Motility; Česká republika; Spermatozoa; Adult; dospělí; mužské pohlaví; variabilita počtu kopií segmentů DNA; Air Pollution; látky znečišťující vzduch; Czech Republic; policie; znečištění ovzduší; lidé; roční období; Seasons; Humans; motilita spermií; spermie; Air Pollutants